(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The theoretical foundations of ensuring the stability of the banking system, including studies based on the theoretical and practical significance of the studies of economists of foreign countries are presented. The theoretical foundations of the concept of stability, research on the issue of achieving the stability of the banking system are presented.